Library readiness in the era of liquid modernity : Analysing the response of IAIN Curup Library to technological dynamics - Rizkyantha, Okky; Tafrikhuddin; Labibah (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. This study explores the responses of academic libraries to technological advancements, focusing on the IAIN Curup Library in Indonesia, and evaluates its adaptation to the evolving dynamics of liquid modernity. Methodology. Using the E-Readiness Assessment Models as a framework, the research examines the library’s technological infrastructure, human resources, regulatory environment, and digital engagement. Result and Discussion. The findings highlight that while the library has established strong technological foundations, including digital repositories and automation systems, there remain significant gaps in its readiness for adopting newer technologies such as artificial intelligence and digital libraries. They already overcame the library's digital competencies with workshops and self-teaching, but its lack of specific AI regulations and librarian skills is also addressed. Conclusion. The study underscores the need for continuous professional development, digital services and the creation of comprehensive policies to facilitate AI integration. The research contributes to understanding how academic libraries can effectively respond to technological changes while maintaining alignment with institutional goals and broader societal shifts toward digital engagement.